Piezoelectric film with metal coating, device, and mass sensing device
Patent Information
- Application Number
- JP2025059488
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本開示の一実施形態によれば、質量検知センサ等のデバイスに適用することが可能な金属膜付き圧電フィルム、それを用いたデバイス、及び質量検知デバイスが提供される。
Smart Images

Figure 2026166514000005 
Figure 2026166514000006 
Figure 2026166514000007
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a piezoelectric film with a metal film, a device, and a mass sensing device. [Background technology]
[0002] Traditionally, PZT (PBZrO3-PbTiO3 solid solution), a ceramic material, has been widely used as a piezoelectric material. However, because PZT contains lead, piezoelectric polymer materials, which have a lower environmental impact and superior flexibility and processability, are increasingly being used.
[0003] The use of optically active polymers such as polypeptides and polylactic acid has attracted attention as piezoelectric polymer materials. Polylactic acid-based polymers are known to exhibit piezoelectricity through mechanical stretching alone, and their piezoelectricity is known to not decrease over several years. Against this backdrop, various piezoelectric polymer materials using polylactic acid have been reported and investigated.
[0004] Patent Document 1 discloses a piezoelectric polymer material comprising an optically active helical chiral polymer with a weight-average molecular weight of 50,000 to 1,000,000, having a crystallinity of 40% to 80% obtained by differential scanning calorimetry (DSC), a transmission haze of 0.0% to 40% for visible light, a normalized molecular orientation MORc of 3.5 to 15.0 when the reference thickness measured by microwave molecular orientation measurement is 50 μm, and a product of the MORc and the crystallinity of 100 to 700. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] International Publication No. 2012 / 026494 [Overview of the project] [Problems that the invention aims to solve]
[0006] The inventors of the present invention conducted thorough research on the above-mentioned piezoelectric polymer material and found that when the mass on the surface of a piezoelectric polymer film containing polylactic acid changes, the resonance frequency shifts accordingly.
[0007] However, in devices fabricated using the piezoelectric polymer film containing polylactic acid described above, the metal thin film used as an electrode tends to peel off from the film substrate, posing a challenge when applied to devices such as mass sensing devices.
[0008] One embodiment of this disclosure aims to solve the problem of providing a piezoelectric film with a metal film that can be applied to devices such as mass sensing sensors, a device using the same, and a mass sensing device. [Means for solving the problem]
[0009] The means for solving the above problems include the following embodiments. <1> The invention comprises a film substrate containing an optically active helical chiral polymer (A), and a metal thin film provided on the film substrate, wherein the film substrate containing the optically active helical chiral polymer (A) has a normalized molecular orientation (MOR) measured by microwave molecular orientation spectroscopy with a reference thickness of 50 μm. c A piezoelectric film with a metal film, having a 3.5-15.0 iontolith, a crystallinity of 20%-80% obtained by DSC method, plasma treatment on at least one surface, and a total haze of 2.0%-20.0%. <2> The aforementioned metal thin film is composed of chromium (Cr) or gold (Au). <1> Piezoelectric film with metal film as described above. <3> The surface roughness R of the plasma-treated surface of the aforementioned film substrate is measured in accordance with JIS B 0031. a The range is 10nm to 50nm. <1> or <2> Piezoelectric film with metal film as described above. <4> The piezoelectric film with a metal film according to any one of <1> to <3>, wherein the optically active helical chiral polymer (A) is a polylactic acid-based polymer having a main chain containing a structural unit represented by the following formula (1).
Chemical Formula
Effects of the Invention
[0010] According to one embodiment of the present disclosure, a piezoelectric film with a metal film that can be applied to devices such as mass detection sensors, a device using the same, and a mass detection device are provided.
Brief Description of the Drawings
[0011] [Figure 1] Figure 1 is a schematic top view showing an example of the structure of the device of the present disclosure (the white arrows in the figure indicate the orientation direction of the uniaxially stretched polylactic acid). [Figure 2] Figure 2 is a schematic diagram showing an experimental system for performance evaluation of the device of the present disclosure. [Figure 3] Figure 3 is a schematic diagram showing the results of performance evaluation of the device of the present disclosure.
Modes for Carrying Out the Invention
[0012] An embodiment of this disclosure is described below. This description is illustrative of an embodiment and does not limit the scope of this disclosure.
[0013] In this disclosure, numerical ranges indicated using "~" represent a range that includes the numbers before and after "~" as the minimum and maximum values, respectively. In numerical ranges described in stages in this disclosure, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In numerical ranges described in this disclosure, the upper or lower limit of that numerical range may be replaced with the values shown in the examples. In this disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes, as long as their intended purpose is achieved.
[0014] <Piezoelectric film with metal coating> The piezoelectric film with a metal film according to this disclosure comprises a film substrate containing an optically active helical chiral polymer (A), and a metal thin film provided on the film substrate. The film substrate containing the optically active helical chiral polymer (A) is The normalized molecular orientation (MORc) measured by microwave molecular orientation measurement is 3.5 to 15.0 when the reference thickness is set to 50 μm. The degree of crystallinity obtained by the DSC method is 20% to 80%. At least one side is plasma treated, The total haze is between 2.0% and 20.0%.
[0015] The above configuration can be applied to devices such as mass detection sensors.
[0016] (Film substrate containing optically active helical chiral polymer (A)) A film substrate containing an optically active helical chiral polymer (A) (hereinafter also simply referred to as "film substrate") contains an optically active helical chiral polymer (A).
[0017] -Optically active helical chiral polymer (A)- Optically active helical chiral polymers are polymers that have a helical molecular structure and possess molecular optical activity. Examples of optically active helical chiral polymers (hereinafter also referred to as "optically active polymers") include polypeptides, cellulose derivatives, polylactic acid resins, polypropylene oxides, and poly(β-hydroxybutyric acid). Examples of the polypeptides mentioned above include poly(γ-benzyl glutarate) and poly(γ-methyl glutarate). Examples of the cellulose derivatives include cellulose acetate and cyanoethylcellulose.
[0018] From the viewpoint of improving the piezoelectricity of the film substrate, the optically active polymer preferably has an optical purity of 95.00%ee or higher, more preferably 99.00%ee or higher, and even more preferably 99.99%ee or higher. Preferably, it is 100.00%ee. By setting the optical purity of the optically active polymer within the above range, the packing properties of the polymer crystals that exhibit piezoelectricity are increased, and as a result, piezoelectricity tends to be enhanced. The optical purity of an optically active polymer is calculated using the following formula. Optical purity (%ee) = 100 × |L volume - D volume | / (L volume + D volume) In other words, the optical purity is defined as the value obtained by multiplying the result of dividing the difference (absolute value) between the amount of the L-isomer (L-isomer) of the optically active polymer and the amount of the D-isomer (D-isomer) of the optically active polymer by the total amount of the L-isomer (L-isomer) and D-isomer (D-isomer) of the optically active polymer by 100. The amounts of the L-isomer (mass%) and D-isomer (mass%) of the optically active polymer will be values obtained using high-performance liquid chromatography (HPLC). Specific measurement details will be described later.
[0019] Among the optically active polymers described above, compounds having a main chain containing a structural unit represented by the following formula (1) are preferred from the viewpoint of increasing optical purity and improving piezoelectricity.
[0020] [ka]
[0021] Examples of compounds having a structural unit represented by formula (1) as the main chain include polylactic acid resins. Among these, polylactic acid is preferred, and homopolymers of L-lactic acid (PLLA) or D-lactic acid (PDLA) are most preferred.
[0022] The aforementioned polylactic acid resin refers to "polylactic acid," "a copolymer of L-lactic acid or D-lactic acid and a copolymerizable polyfunctional compound," or a mixture thereof. The aforementioned "polylactic acid" is a polymer formed by the polymerization of lactic acid via ester bonds, and is known to be produced by methods such as the lactide method, which proceeds via lactide, and the direct polymerization method, in which lactic acid is heated under reduced pressure in a solvent while removing water during polymerization. Examples of the aforementioned "polylactic acid" include L-lactic acid homopolymers, D-lactic acid homopolymers, block copolymers containing polymers of at least one of L-lactic acid and D-lactic acid, and graft copolymers containing polymers of at least one of L-lactic acid and D-lactic acid.
[0023] The aforementioned "copolymerizable polyfunctional compounds" include hydroxycarboxylic acids such as glycolic acid, dimethylglycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxypropanoic acid, 3-hydroxypropanoic acid, 2-hydroxyvaleric acid, 3-hydroxyvaleric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, 2-hydroxycaproic acid, 3-hydroxycaproic acid, 4-hydroxycaproic acid, 5-hydroxycaproic acid, 6-hydroxycaproic acid, 6-hydroxymethylcaproic acid, mandelic acid, glycolides, cyclic esters such as β-methyl-δ-valerolactone, γ-valerolactone, ε-caprolactone, oxalic acid, malonic acid, succinic acid, glutaric acid, and adipine. Examples include acids, polycarboxylic acids such as pimelic acid, azelaic acid, sebacic acid, undecanediol, dodecanediol, and terephthalic acid, and their anhydrides, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, tetramethylene glycol, and polyhydric alcohols such as 1,4-hexanedimethanol, polysaccharides such as cellulose, and aminocarboxylic acids such as α-amino acids.
[0024] Examples of the aforementioned "copolymer of a polyfunctional compound copolymerizable with lactic acid" include block copolymers or graft copolymers having a polylactic acid sequence capable of generating helical crystals. The aforementioned polylactic acid resin can be produced, for example, by a method of directly dehydrating and condensing lactic acid as described in Japanese Patent Publication No. 59-096123 and Japanese Patent Publication No. 7-033861, or by a method of ring-opening polymerization using lactide, which is a cyclic dimer of lactic acid, as described in U.S. Patent Nos. 2,668,182 and 4,057,357, etc. Furthermore, in order to achieve an optical purity of 95.00%ee or higher for the optically active polymers obtained by each of the above manufacturing methods, it is preferable, for example, when producing polylactic acid by the lactide method, to polymerize lactide whose optical purity has been improved to 95.00%ee or higher by crystallization.
[0025] The optically active polymer according to this embodiment may have a weight-average molecular weight (Mw) of 50,000 to 1,000,000. If the lower limit of the weight-average molecular weight of the optically active polymer is less than 50,000, the mechanical strength of the molded article made from the optically active polymer will be insufficient. Preferably, the lower limit of the weight-average molecular weight of the optically active polymer is 100,000 or more, and more preferably 200,000 or more. On the other hand, if the upper limit of the weight-average molecular weight of the optically active polymer exceeds 1,000,000, it becomes difficult to mold the molded article made from the optically active polymer, such as by extrusion molding of films. Preferably, the upper limit of the weight-average molecular weight is 800,000 or less, and more preferably 300,000 or less. Furthermore, the molecular weight distribution (Mw / Mn) of the optically active polymer is preferably 1.1 to 5, more preferably 1.2 to 4, and even more preferably 1.4 to 3, from the viewpoint of the strength of the film substrate. The weight-average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of polylactic acid polymers are measured using gel permeation chromatography (GPC) according to the GPC measurement method described below.
[0026] -GPC measurement device- Waters GPC-100 -column- Shodex LF-804, manufactured by Showa Denko Corporation. -Sample Preparation- Dissolve the polylactic acid polymer in a solvent (e.g., chloroform) at 40°C to prepare a sample solution with a concentration of 1 mg / ml.
[0027] -Measurement conditions- 0.1 ml of the sample solution is introduced into the column with chloroform as the solvent, at a temperature of 40°C, and at a flow rate of 1 ml / min. The sample concentration in the sample solution separated by column chromatography is measured using a differential refractometer. A universal calibration curve is created using polystyrene standard samples, and the weight-average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polylactic acid polymer are calculated. The polylactic acid polymer may be a commercially available polylactic acid, such as PURASORB (PD, PL) from PURAC Corporation or LACEA (H-100, H-400) from Mitsui Chemicals Corporation. When using polylactic acid-based resins as optically active polymers, it is preferable to produce the optically active polymers by the lactide method or direct polymerization method in order to achieve a weight-average molecular weight (Mw) of 50,000 or more of the polylactic acid-based resin.
[0028] -Other ingredients- The film substrate according to this embodiment may contain other components besides the helical chiral polymer, such as known resins represented by polyethylene resin and polystyrene resin; inorganic fillers such as silica, hydroxyapatite, and montmorillonite; and known nucleating agents such as phthalocyanine, to the extent that the effects of this embodiment are not impaired.
[0029] --Inorganic filler-- For example, in order to make the film substrate a transparent film that suppresses the generation of voids such as air bubbles, inorganic fillers such as hydroxyapatite may be nano-dispersed in the film substrate. However, nano-dispersing inorganic fillers requires a large amount of energy to break down aggregates, and if the fillers are not nano-dispersed, the transparency of the film may decrease. When the film substrate according to this embodiment contains inorganic fillers, it is preferable that the amount of inorganic fillers relative to the total mass of the film substrate be less than 1% by mass. Furthermore, if the film substrate contains components other than helical chiral polymers, the content of these components is preferably 20% by mass or less, and more preferably 10% by mass or less, relative to the total mass of the film substrate.
[0030] --Crystal Nucleating Agent-- While the nucleating agent is not particularly limited as long as it is found to have a crystallization-promoting effect, it is desirable to select a substance with a crystal structure that has interplanar spacing similar to that of the polylactic acid crystal lattice. This is because substances with similar interplanar spacing are more effective as nucleating agents. Examples include organic substances such as zinc phenylsulfonate, melamine polyphosphate, melamine cyanurate, zinc phenylphosphonate, calcium phenylphosphonate, and magnesium phenylphosphonate, as well as inorganic substances such as talc and clay. Among these, zinc phenylphosphonate is preferred because its interplanar spacing is most similar to that of polylactic acid and it provides a good crystal formation promoting effect. Commercially available nucleating agents can be used. Specifically, examples include zinc phenylphosphonate; EcoPromote (manufactured by Nissan Chemical Industries, Ltd.).
[0031] The content of the nucleating agent is typically 0.01 to 1.0 parts by mass, preferably 0.01 to 0.5 parts by mass, per 100 parts by mass of helical chiral polymer, and particularly preferably 0.02 to 0.2 parts by mass from the viewpoint of better crystallization promotion effect and maintenance of biomass content. If the above content of the nucleating agent is less than 0.01 parts by mass, the effect of promoting crystallization is insufficient, and if it exceeds 1.0 part by mass, it becomes difficult to control the rate of crystallization, and the transparency of the film substrate tends to decrease. Furthermore, from the viewpoint of transparency, it is preferable that the film substrate does not contain any components other than helical chiral polymers.
[0032] -Manufacturing of film substrates- The film substrate according to this embodiment is obtained by mixing a helical chiral polymer, such as the polylactic acid polymer described above, with other components as needed to form a mixture. The mixture is preferably melt-kneaded. Specifically, for example, when mixing two types of helical chiral polymers, or when mixing the aforementioned inorganic fillers or crystal nucleating agents with helical chiral polymers, the helical chiral polymers to be mixed are melt-kneaded for 5 to 20 minutes using a melt-kneader [Laboplast Mixer, manufactured by Toyo Seiki Co., Ltd.] at a mixer rotation speed of 30 rpm to 70 rpm and a temperature of 180°C to 250°C. This process yields a blend of multiple types of helical chiral polymers or a blend of helical chiral polymers with other components such as inorganic fillers.
[0033] -Method for manufacturing film-based materials- The film substrate according to this embodiment can be manufactured by a manufacturing method that includes, for example, a first step of heating an amorphous sheet containing a helical chiral polymer to obtain a pre-crystallized sheet, and a second step of stretching the pre-crystallized sheet mainly in a uniaxial direction. Generally, increasing the force applied to a film during stretching promotes the orientation of helical chiral polymers, increasing the piezoelectric constant, promoting crystallization, and increasing the crystal size, which tends to increase haze. Furthermore, the dimensional deformation rate also tends to increase due to the increase in internal stress. Simply applying force to a film results in the formation of unoriented crystals, such as spherulites. While these poorly oriented crystals increase internal haze, they do not significantly contribute to increasing the piezoelectric constant. Therefore, to form a film with a high piezoelectric constant and low internal haze and dimensional deformation rate, it is necessary to efficiently form oriented crystals that contribute to the piezoelectric constant at a minute size that does not increase internal haze. In the method for manufacturing the film substrate of the present invention, for example, the sheet is precrystallized before stretching to form fine crystals, and then stretched. This allows the force applied to the film during stretching to be efficiently applied to the less crystalline polymer portions between the microcrystals, and the helical chiral polymer can be efficiently oriented in the main stretching direction. Specifically, fine oriented crystals are formed within the less crystalline polymer portions between the microcrystals, and at the same time, the spherulites formed by precrystallization break down, and the lamellar crystals constituting the spherulites are oriented in the stretching direction in a chain-like manner connected by tie molecular chains, thereby achieving a desired MOR value.c This allows us to obtain sheets with low haze and dimensional deformation rates without significantly reducing the piezoelectric constant. Normalized Molecular Orientation (MOR) c To control this, it is important to adjust the heat treatment time and heat treatment temperature in the first step, and the stretching speed and stretching temperature in the second step. As mentioned above, helical chiral polymers are polymers with molecular optical activity whose molecular structure is helical. Amorphous sheets containing helical chiral polymers may be commercially available or may be manufactured by known film molding methods such as extrusion molding. The amorphous sheet may be single-layer or multi-layer.
[0034] --First step (preliminary crystallization step)-- Pre-crystallized sheets can be obtained by heating and crystallizing an amorphous sheet containing a helical chiral polymer. Specifically, 1) an amorphous sheet may be crystallized by heat treatment and then sent to the stretching process (second process) described later, set in the stretching apparatus, and stretched (offline heat treatment), or 2) an amorphous sheet that has not been crystallized by heat treatment may be set in the stretching apparatus, heated in the stretching apparatus to pre-crystallize it, and then continuously sent to the stretching process (second process) and stretched (in-line heat treatment). The heat treatment temperature T for precrystallizing a sheet containing an amorphous helical chiral polymer is not particularly limited, but in order to enhance the piezoelectric properties and transparency of the film substrate produced by this manufacturing method, it is preferable to set the temperature such that the relationship between the glass transition temperature Tg of the helical chiral polymer and the following equation is satisfied, and the degree of crystallinity is 10% to 70%. Tg ≤ T ≤ Tg + 40°C (Tg represents the glass transition temperature of the helical chiral polymer material.)
[0035] The heat treatment time for pre-crystallization is such that the desired degree of crystallinity is achieved and the normalized molecular orientation of the film substrate after stretching (after the second step) is determined. cThe product of the temperature and the degree of crystallinity of the stretched film substrate should be adjusted to be 100 to 700, preferably 125 to 650, and more preferably 250 to 350. A longer heat treatment time results in a higher degree of crystallinity after stretching, and a higher normalized molecular orientation MORc after stretching. A shorter heat treatment time results in a lower degree of crystallinity after stretching, and a lower normalized molecular orientation MORc after stretching. c It will also decrease.
[0036] When the crystallinity of the pre-crystallized sheet before stretching increases, the sheet hardens and greater stretching stress is applied to the sheet, so even the parts of the sheet with relatively low crystallinity become more oriented, resulting in normalized molecular orientation (MOR) after stretching. c This also increases. Conversely, if the degree of crystallinity of the pre-crystallized sheet before stretching is low, the sheet becomes softer and less stretching stress is applied to the sheet, so the orientation of the relatively low crystallinity parts of the sheet also weakens, and the normalized molecular orientation MOR after stretching increases. c It is also expected that the level will decrease.
[0037] The heat treatment time varies depending on the heat treatment temperature, the sheet thickness, the molecular weight of the resin constituting the sheet, and the type or amount of additives. Furthermore, the actual heat treatment time required to crystallize the sheet is equivalent to the sum of the preheating time and the heat treatment time in the preliminary crystallization step before preheating, if preheating is performed at a temperature at which the amorphous sheet crystallizes during the preheating step which may be performed before the stretching step (second step) described later. The heat treatment time for amorphous sheets is usually 5 seconds to 60 minutes, but from the viewpoint of stabilizing manufacturing conditions, it may be 1 minute to 30 minutes. For example, when precrystallizing amorphous sheets containing polylactic acid resin as a helical chiral polymer, it is preferable to heat at 60°C to 170°C for 5 seconds to 60 minutes, but it may also be 1 minute to 30 minutes.
[0038] To efficiently impart piezoelectricity, transparency, and high dimensional stability to the stretched sheet, it is important to adjust the crystallinity of the pre-crystallized sheet before stretching. That is, the reason why piezoelectricity and dimensional stability are improved by stretching is that the stress from stretching concentrates on the relatively high crystallinity portions in the pre-crystallized sheet, which is presumed to be in a spherulitic state, and the spherulites are oriented while being destroyed, thereby increasing the piezoelectric d 14 On the other hand, the stretching stress is applied to the relatively low crystallinity portions via the spherulites to promote orientation, thereby increasing the piezoelectric d 14 This is considered to be the reason for the improvement.
[0039] The crystallinity of the stretched sheet is set to be 20% to 80%, preferably 40% to 70%. Therefore, the crystallinity of the pre-crystallized sheet immediately before stretching is set to be 3% to 70%, preferably 10% to 60%, and more preferably 15% to 50%. The crystallinity of the pre-crystallized sheet may be measured in the same manner as the measurement of the crystallinity of the stretched film base material.
[0040] The thickness of the pre-crystallized sheet is mainly determined by the thickness of the film base material to be obtained by stretching in the second step and the stretching ratio, and is preferably 50 μm to 1,000 μm, more preferably about 200 μm to 800 μm.
[0041] --Second step (stretching step)-- The stretching method in the stretching step, which is the second step, is not particularly limited, and various stretching methods such as uniaxial stretching, biaxial stretching, and solid-phase stretching described later can be used. By stretching the film base material, a film base material with a large main surface area can be obtained. Here, the "main surface" refers to the surface with the largest area among the surfaces of the film base material. The film base material may have two or more main surfaces. For example, when the film base material is a plate-like body having two surfaces each of surface A of 10 mm × 0.3 mm, surface B of 3 mm × 0.3 mm, and surface C of 10 mm × 3 mm, the main surface of the film base material is surface C, and the film base material has two main surfaces. In this embodiment, a large main surface area means that the main surface area of the film substrate is 5 mm². 2 This means that it is greater than 10mm 2 It is preferable that the above conditions are met.
[0042] Furthermore, "solid-phase stretching" refers to "stretching at a temperature higher than the glass transition temperature Tg of the film substrate and lower than the melting point Tm of the film substrate, under a compressive stress of 5 MPa to 10,000 MPa," which can further improve the piezoelectric properties of the film substrate, as well as its transparency and elasticity. It is presumed that by solid-phase stretching or primarily unidirectional stretching of the film substrate, the molecular chains of the polylactic acid-based polymer contained in the film substrate can be oriented in one direction and aligned at a high density, thereby obtaining higher piezoelectricity. Here, the glass transition temperature Tg [°C] and the melting point Tm [°C] of the film substrate are obtained from the melting endothermic curve when the temperature of the film substrate is increased at a heating rate of 10°C / min using the differential scanning calorimeter (DSC), with the glass transition temperature (Tg) being the point where the curve inflates and the temperature (Tm) being confirmed as the peak value of the endothermic reaction being obtained.
[0043] When stretching the film substrate using only tensile force, such as in uniaxial stretching or biaxial stretching methods, the stretching temperature of the film substrate is preferably in a temperature range about 10°C to 20°C higher than the glass transition temperature of the film substrate. In the case of solid-phase drawing, the compressive stress is preferably 50 MPa to 5000 MPa, and more preferably 100 MPa to 3000 MPa. The stretching ratio in the stretching process is preferably 3 to 30 times, and more preferably in the range of 4 to 15 times. The solid-phase stretching of the pre-crystallized sheet is performed by applying pressure to the film substrate, for example, by sandwiching it between rolls or a burette.
[0044] When stretching a pre-crystallized sheet, preheating may be performed immediately before stretching to make the sheet easier to stretch. Generally, this preheating is done to soften the sheet before stretching and make it easier to stretch, and is usually performed under conditions that do not crystallize the sheet before stretching and harden it. However, as described above, in this embodiment, pre-crystallization is performed before stretching, so the preheating may also be performed to perform pre-crystallization. Specifically, by performing preheating at a higher temperature or for a longer time than normally performed, in accordance with the heating temperature and heat treatment time in the pre-crystallization process described above, preheating and pre-crystallization can be performed together.
[0045] --Annealing process-- From the viewpoint of improving the piezoelectric constant, it is preferable to subject the film substrate, after stretching, to a certain heat treatment (hereinafter also referred to as "annealing treatment"). The annealing temperature is preferably approximately 80°C to 160°C, and more preferably 100°C to 155°C. The method for applying temperature during the annealing process is not particularly limited, but examples include direct heating using a hot air heater or infrared heater, or immersing the film substrate in a heated liquid such as heated silicone oil. In this case, if the film substrate deforms due to linear expansion, it becomes difficult to obtain a practically flat film. Therefore, it is preferable to apply a constant tensile stress (for example, 0.01 MPa to 100 MPa) to the film substrate and apply temperature while preventing the film substrate from sagging.
[0046] The temperature application time for the annealing process is preferably 1 second to 60 minutes, more preferably 1 second to 300 seconds, and even more preferably heated in the range of 1 second to 60 seconds. If annealing is performed for more than 60 minutes, the degree of orientation may decrease due to the growth of spherulites from the molecular chains of the amorphous portion at a temperature higher than the glass transition temperature of the film substrate, which may result in a decrease in piezoelectricity. The film substrate annealed as described above is preferably rapidly cooled after the annealing process. In the annealing process, "rapid cooling" means that immediately after the annealing process, the annealed film substrate is immersed in, for example, ice water to cool it to at least below its glass transition temperature (Tg), and that no other processing is involved between the annealing process and the immersion in ice water.
[0047] Methods of rapid cooling include immersing the annealed film substrate in a refrigerant such as water, ice water, ethanol, ethanol or methanol containing dry ice, or liquid nitrogen, or spraying it with a liquid spray with low vapor pressure to cool it by latent heat of vaporization. To continuously cool the film substrate, it is possible to rapidly cool it by bringing it into contact with a metal roll controlled to a temperature below the glass transition temperature (Tg) of the film substrate. Furthermore, the cooling process may be performed only once or two or more times, and it is also possible to alternate between annealing and cooling.
[0048] -Physical properties of film substrates- -- Normalized Molecular Orientation (MOR) c . The film substrate according to this embodiment is normalized molecular orientation MOR c The ratio is preferably 3.5 to 15.0, more preferably 4.0 to 15.0, even more preferably 6.0 to 10.0, and even more preferably 7 to 10.0. Normalized molecular orientation MOR c If the value is in the range of 3.5 to 15.0, there will be many polylactic acid molecular chains aligned in the stretching direction, resulting in a higher rate of oriented crystal formation and enabling the expression of high piezoelectricity.
[0049] Molecular Orientation Ratio (MOR) is a value that indicates the degree of molecular orientation and is measured by the following microwave molecular orientation measurement method. Specifically, the sample (film) is placed in the microwave resonant waveguide of a microwave molecular orientation analyzer (transmission molecular orientation analyzer) so that the sample surface (film surface) is perpendicular to the direction of microwave propagation. Then, while the sample is continuously irradiated with microwaves whose vibration direction is biased in one direction, the sample is rotated from 0° to 360° in a plane perpendicular to the direction of microwave propagation, and the molecular orientation degree (MOR) is determined by measuring the microwave intensity transmitted through the sample. Normalized molecular orientation MOR in this embodiment c This refers to the standard thickness t. c This is the MOR value when the saturation is set to 50 μm, and can be calculated using the following formula. MOR c = ( t c / t) × (MOR-1) + 1 (t c : Reference thickness to be corrected, t: Sample thickness) Normalized Molecular Orientation (MOR) c This can be measured at a resonant frequency of around 4 GHz or 12 GHz using a molecular orientation analyzer (for example, the microwave molecular orientation analyzer MOA-2012A or MOA-6000 manufactured by Oji Instruments Co., Ltd.). Normalized Molecular Orientation (MOR) c As described later, this can be controlled mainly by the heat treatment conditions (heating temperature and heating time) and stretching conditions (stretching temperature and stretching speed) of the uniaxially oriented film before stretching.
[0050] --Degree of Crystallinity-- The degree of crystallinity of the film substrate according to this embodiment is determined by the DSC method, and the degree of crystallinity of the film substrate is 20% to 80%, with 40% to 70% being preferred. If the degree of crystallinity is within this range, the piezoelectric properties and transparency of the film substrate are well balanced, and whitening and breakage are less likely to occur when the film substrate is stretched, making it easy to manufacture. The degree of crystallinity is determined from the melting endothermic curve when measured using a differential scanning calorimeter (DSC; for example, a DSC-1 manufactured by PerkinElmer) at a heating rate of 10°C / min.
[0051] --Plasma treatment-- In the piezoelectric film with a metal film of this embodiment, at least one surface of the film substrate is plasma-treated. Plasma treatment makes the chemical and physical state (surface roughness) of the film substrate surface suitable for improving adhesion with the metal thin film. As a result, the metal thin film does not peel off from the surface of the film substrate in the piezoelectric film with a metal film of this embodiment. Therefore, it can be applied to devices such as mass sensing sensors.
[0052] Plasma treatments include, for example, those using hydrogen, argon, nitrogen, and oxygen gases. Plasma treatment can be performed using one or more gases selected from these, but plasma treatment using oxygen gas is particularly preferred from the viewpoint of making the chemical and physical state (surface roughness) of the film substrate surface suitable for improving adhesion with the metal thin film. Plasma treatment using oxygen gas can chemically modify not only the physical state (surface roughness) of the substrate surface but also the chemical state of the film substrate surface, making it suitable for improving adhesion with the metal thin film. Plasma treatment using oxygen gas is expected to desorb gas components released from the surface of the film substrate (so-called outgassing, e.g., CO2) or gas components adsorbed on the surface of the film substrate (e.g., CO2) from the surface of the film substrate, thereby improving the adhesion of the metal thin film to the film substrate during the formation of the metal thin film (e.g., during sputtering).
[0053] Plasma treatment can be performed by injecting gases such as hydrogen, argon, nitrogen, and oxygen at a predetermined gas flow rate under reduced pressure conditions and irradiating them with plasma.
[0054] The plasma irradiation output in plasma processing may be, for example, 10W to 1,000W. From the viewpoint of making the chemical and physical state (surface roughness) of the film substrate surface suitable for improving adhesion with the metal thin film, it is preferably 50W to 500W, more preferably 75W to 300W, and even more preferably 100W to 200W.
[0055] The processing time in plasma treatment may be, for example, 0.1 minutes to 30 minutes. From the viewpoint of making the chemical and physical state (surface roughness) of the surface of the film substrate suitable for improving adhesion with the metal thin film, it is preferably 0.5 minutes to 20 minutes, more preferably 1 minute to 10 minutes, and even more preferably 2 minutes to 5 minutes.
[0056] The flow rates of each gas in the plasma treatment may be, for example, 5 sccm to 50 sccm.
[0057] Plasma treatment is preferably performed at a temperature of 85°C or lower so as not to affect the piezoelectric properties of the film substrate.
[0058] --All Haze-- In the piezoelectric film with a metal film of this embodiment, the total haze of the film substrate is 2.0% to 20.0%, preferably 2.6% to 20.0%, more preferably 3.4% to 20.0%, and even more preferably 4.0% to 20.0%. A total haze of 2.0% to 20.0% exhibits the desired transparency and piezoelectric properties.
[0059] "Total haze" refers to the total light transmittance (T) which represents the total amount of light transmitted when light is irradiated onto the film substrate layer. t ) and the diffuse light transmittance (T) of light diffused and transmitted by the film substrate layer. d From the ratio of ), total haze (%) = (T d / T t This value is obtained by multiplying by ) × 100.
[0060] Total light transmittance (T t ) is the transmittance of parallel light rays that are transmitted while remaining coaxial with the incident light (T p ) and diffuse light transmittance (T d It is the sum of (T). Total light transmittance (T t ) and diffuse light transmittance (T dThis value is measured using a haze meter ("HAZE METER NDH5000SP" manufactured by Nippon Denshoku Co., Ltd.) in accordance with JIS K 7361.
[0061] --Surface roughness R a . In the piezoelectric film with a metal film of this embodiment, the surface roughness R of the plasma-treated surface of the film substrate is measured in accordance with JIS B 0031. a From the viewpoint of improving adhesion with the metal thin film, the surface roughness is preferably 10 nm to 50 nm, more preferably 20 nm to 45 nm, and even more preferably 25 nm to 40 nm. When the surface roughness is 10 nm to 50 nm, the adhesion between the film substrate and the metal thin film is easily improved due to the anchoring effect. The surface roughness is the arithmetic mean of three arbitrarily measured values.
[0062] --Internal Haze-- In the piezoelectric film with a metal film of this embodiment, the internal haze of the film substrate is preferably 0.2% to 1%, and more preferably 0.3% to 0.8%.
[0063] The internal haze is the value measured at 25°C using a haze measuring instrument (TC-HIII DPK, manufactured by Tokyo Denshoku Co., Ltd.) in accordance with JIS-K7105 for a film substrate with a thickness of 0.05 mm. Details of the measurement method will be described later in the examples.
[0064] The internal haze of the film substrate is preferable as low as possible, but from the viewpoint of balancing with the piezoelectric constant, it is preferably 0.2% to 1.0%, and more preferably 0.3% to 0.8%. Internal haze refers to the haze excluding the haze caused by the shape of the outer surface of the film substrate, as will be described later in the examples. The transparency of the film substrate can be evaluated, for example, by visual observation or internal haze measurement.
[0065] -Metal Thin Film- The piezoelectric film with a metal film of this embodiment comprises a metal thin film provided on a film substrate. Examples of the metal thin film include conductive materials such as aluminum (Al), nickel (Ni), titanium (Ti), copper (Cu), chromium (Cr), and gold (Au). From the viewpoint of adhesion to the film substrate, the metal thin film is preferably composed of chromium (Cr) or gold (Au).
[0066] Thin metal films can be formed by vacuum deposition or sputtering.
[0067] In vacuum deposition, a metal source and a film substrate are placed opposite each other in a vacuum chamber, and the metal source is heated to evaporate or sublimate, depositing it onto the surface of the film substrate. In the sputtering method, a metal target and a film substrate are placed facing each other in a vacuum chamber, and an inert gas is supplied while a voltage is applied. Inert gas ions are accelerated and irradiated onto the metal target, ejecting the target material from the surface of the metal target and depositing it on the surface of the film substrate.
[0068] In manufacturing the piezoelectric film with a metal film according to this embodiment, the method for forming the metal thin film is not particularly limited, but sputtering is preferred from the viewpoint of easily reducing the thickness of the metal thin film. The thickness of the metal thin film may be, for example, 1 nm to 50 nm, 3 nm to 30 nm, or 5 nm to 20 nm.
[0069] The formation of the metal thin film is preferably carried out at a temperature of 85°C or lower so as not to affect the piezoelectric properties of the film substrate.
[0070] <device> The device of this embodiment uses the piezoelectric film with a metal film of this embodiment. As described above, the metal film-coated piezoelectric film of this embodiment does not have the metal film peel off from the surface of the film substrate. Therefore, it can be applied to devices such as speakers, touch panels (smartphones, projectors, etc.), headphones, microphones, underwater microphones, ultrasonic transducers, ultrasonic measuring instruments, piezoelectric vibrators, mechanical filters, piezoelectric transformers, delay devices, sensors, acceleration sensors, shock sensors, vibration sensors, pressure sensors, tactile sensors, electric field sensors, sound pressure sensors, displays, fans, pumps, variable focus mirrors, sound insulation materials, soundproofing materials, keyboards, audio equipment, information processing machines, measuring instruments, medical equipment, biosensors, gas sensors, and mass detection sensors.
[0071] The device of this embodiment may be obtained by processing a piezoelectric film with a metal film using photolithography. As described above, the piezoelectric film with a metal film of this embodiment does not have the metal film peel off from the surface of the film substrate. Therefore, it can be processed using photolithography and applied to devices such as mass sensing sensors.
[0072] The photolithography process may include steps such as: laminating a photoresist onto the side of a piezoelectric film with a metal film where the metal film is not formed; laminating a photomask processed into a desired device shape onto the piezoelectric film with the photoresist laminated on it; selectively irradiating the photomask with active energy rays; developing the photomask after exposure to obtain a resist pattern; and etching.
[0073] In terms of device shape, ring-shaped, tape-shaped, or rectangular shapes are preferred, from the viewpoint that the piezoelectric film is easily resonant and suitable for application to devices such as mass sensing sensors.
[0074] Photolithography processing is preferably carried out at a temperature of 85°C or lower to avoid affecting the piezoelectric properties of the film substrate.
[0075] <Mass sensing device> The mass detection device of this embodiment is constructed using the device of this embodiment. As long as the mass detection device of this embodiment is constructed using the aforementioned device, there are no particular restrictions on its configuration, and it can be configured in various ways. [Examples]
[0076] The embodiments of this disclosure will be described in detail below with reference to examples. The embodiments of this disclosure are not limited to the following examples.
[0077] <Example 1> (Fabrication of piezoelectric film with metal coating) - Preparation of film substrates containing optically active helical chiral polymers (A) - A polylactic acid resin (registered trademark LACEA, H-400 (weight-average molecular weight Mw: 200,000; optically active helical chiral polymer (A))) manufactured by Mitsui Chemicals, Inc. was melt-kneaded at 230°C in an extruder, then extruded from a T-die to form a 300 μm thick raw material sheet, which was then wound onto a cast roll at a surface temperature of 58°C. Next, the raw material sheet was cut to 7 cm in the TD direction and 13 cm in the MD direction. This raw material film was then sandwiched between two 150 mm square, 0.15 mm thick aluminum plates and heated at 90°C for 2 minutes to pre-crystallize, thereby creating a crystallized raw material (pre-crystallization process). Next, the obtained crystallized raw material was set in the chucks of a tensile testing machine with a constant temperature chamber, with two opposing sides of the film. The film width was 7 cm and the distance between the chucks was 30 mm. After setting the raw material, the film surface temperature was raised from room temperature to the constant temperature chamber's set temperature of 80°C. Immediately after reaching 80°C, stretching was started at a stretching speed of 100 mm / min, and uniaxial stretching was performed to a stretching ratio of 4.1 times to obtain a uniaxially oriented film with a thickness of 0.05 mm. The aforementioned uniaxially oriented film was sandwiched between two sheets of #1500 grit sandpaper, and then sandwiched between two 0.15 mm thick aluminum plates to create a five-layer laminate. This laminate was placed in an envelope-shaped vacuum pack made of 50 μm thick polyimide film, and the inside was degassed using a vacuum pump to create a vacuum. This vacuum pack was then inserted between the upper and lower plates of a hot press set to 150°C with a gap of 1 mm. After inserting the film, it was annealed for 10 minutes to produce a 50 μm thick film substrate.
[0078] Normalized molecular orientation (MOR) of film substrates c The reference thickness t was measured using a microwave molecular orientation analyzer MOA-6000 manufactured by Oji Instruments Co., Ltd. c The setting was changed to 50 μm. The degree of crystallinity of the film substrate was determined by accurately weighing 10 mg of the sample and measuring it using a differential scanning calorimeter (PerkinElmer DSC-1) at a heating rate of 10°C / min, and obtained from the melting endothermic curve.
[0079] -Plasma treatment- Next, the fabricated film substrate (shape: 50mm x 50mm x 50μm) was placed in a vacuum chamber (SFA-600 manufactured by Mori Engineering Co., Ltd.), and oxygen plasma treatment was performed on one side at a time with an output of 100W and a holding time of 5 minutes, resulting in a film substrate with both sides treated with oxygen plasma.
[0080] The surface roughness of the oxygen plasma-treated film substrate was measured using a surface roughness meter (contact-type step meter ET200, manufactured by Kosaka Research Institute Co., Ltd.) in accordance with JIS B 0031. a The arithmetic mean was 32 nm. The total haze of oxygen plasma-treated film substrates was measured using a haze meter ("HAZE METER NDH5000SP" manufactured by Nippon Denshoku Co., Ltd.). The internal haze of an oxygen plasma-treated film substrate was measured by measuring the light transmittance in the thickness direction using the following apparatus under the following measurement conditions.
[0081] Internal haze (hereinafter also referred to as internal haze (H1)) was obtained by first measuring the haze (H2) by placing only silicone oil (Shin-Etsu Silicone (trademark), model number: KF96-100CS, manufactured by Shin-Etsu Chemical Co., Ltd.) between two glass plates, and then measuring the haze (H3) by placing a film uniformly coated with silicone oil between two glass plates, and taking the difference between these two values as shown in the formula below. Internal haze (H1) = haze (H3) - haze (H2) To measure the haze value, internal haze (H1) was calculated by measuring the light transmittance in the thickness direction using the following apparatus under the following measurement conditions, and haze (H2) and haze (H3) were also measured. Measuring device: HAZE METER TC-HIIIDPK, manufactured by Tokyo Denshoku Co., Ltd. Sample size: 30mm wide x 30mm long, 0.05mm thick Measurement conditions: In accordance with JIS-K7105 Measurement temperature: room temperature (25℃)
[0082] -Formation of thin metal films- Next, in order to form metal thin films on both sides of the oxygen plasma-treated film substrate, a sputtering apparatus (Shibaura Electrotech Co., Ltd. "CFS-4ES-232") was used to form a 5nm thick Cr thin film with a Cr target and an input power of 100W. Then, the target was changed to Au, and a 20nm thick Au thin film was formed with an input power of 100W.
[0083] As described above, a piezoelectric film with a metal film was obtained.
[0084] (Device fabrication) To microfabricate the device shape of a piezoelectric film with a metal film, in which a thin metal film of Cr or Au is formed on both sides of a film substrate, using photolithography, a 25 μm thick resist film (RY5125 manufactured by Resonaq Corporation) was applied to both sides of the piezoelectric film with a metal film using a hand roller. Next, using an aligner (EVG620 manufactured by EVG), UV exposure dose: 300 mJ / cm²2 The photomask pattern was then transferred to the photoresist film to obtain the device structure shown in Figure 1. Next, developer (1.0 wt% Na2CO3) was added to the beaker, and the substrate was immersed in it at 30°C for approximately 2 minutes to develop and remove any unwanted photoresist film. Next, 50 sccm of oxygen was flowed through a cylindrical plasma etching apparatus (cylindrical electrode structure, chamber diameter: 18 cm), and oxygen radicals were generated by applying a 13.56 MHz RF at a power of 130 W. An etching rate of 5 μm / h was obtained on a film substrate. Finally, the photoresist film was removed by immersing the sample in ethanol for about 30 minutes.
[0085] In this way, a device fabricated using photolithography was obtained.
[0086] Furthermore, the plasma treatment, sputtering treatment, and photolithography processing were each performed at temperatures below 85°C to avoid affecting the piezoelectric properties of the polylactic acid.
[0087] (Device performance evaluation) To evaluate the performance of the obtained device as a resonant device, the experimental system shown in Figure 2 was constructed, and the output voltage due to the piezoelectric effect of the device was monitored when the device was mechanically forced to vibrate using a PZT oscillator. Simultaneously, the vibration displacement in the thickness direction was monitored using a laser Doppler apparatus (Polytec "MSA-500"). The output voltage was observed after being amplified to a gain of 100 using an instrumentation amplifier (INA826). The results are shown in Table 1 and Figure 3.
[0088] <Comparative Example 1> The device was fabricated and evaluated using the same method as in Example 1, except that oxygen plasma treatment was not performed. The results are shown in Table 1.
[0089] [Table 1]
[0090] As shown in Table 1, in Comparative Example 1, the metal thin film (electrode) peeled off from the film substrate after the device was fabricated, making photolithography processing impossible. On the other hand, in Example 1, the metal thin film (electrode) did not peel off from the film substrate, and a device processed by photolithography was obtained.
[0091] The graph at the top of Figure 3 shows the vibration displacement in the thickness direction of the cantilever portion of the device when the forced vibration frequency by PZT is swept from 1 kHz to 100 kHz. The graph at the bottom of Figure 3 shows the output voltage (effective value [Vrms]) due to the piezoelectric effect of the device, which was measured simultaneously.
[0092] As can be seen from Figure 3, in the device of Example 1, resonance occurred in the cantilever portion in the frequency bands around 18kHz to 19kHz and around 33kHz to 34kHz, and a large amplitude output voltage was observed. This confirms that the piezoelectric film with a metal film of this embodiment can be applied to devices such as mass sensing sensors that utilize resonance.
Claims
1. A film substrate containing an optically active helical chiral polymer (A), A thin metal film provided on the aforementioned film substrate, Equipped with, The film substrate containing the optically active helical chiral polymer (A) is Normalized molecular orientation (MOR) when the reference thickness measured by microwave molecular orientation measurement method is 50 μm c The range is 3.5 to 15.
0. The degree of crystallinity obtained by the DSC method is 20% to 80%. At least one side is plasma treated, The total haze is between 2.0% and 20.0%. Piezoelectric film with metal coating.
2. The piezoelectric film with a metal film according to claim 1, wherein the metal thin film is composed of chromium (Cr) or gold (Au).
3. The surface roughness R of the plasma-treated surface of the aforementioned film substrate is measured in accordance with JIS B 0031. a A piezoelectric film with a metal film according to claim 1, wherein the wavelength is 10 nm to 50 nm.
4. The piezoelectric film with a metal film according to claim 1, wherein the optically active helical chiral polymer (A) is a polylactic acid-based polymer having a main chain containing a structural unit represented by the following formula (1). 【Chemistry 1】
5. The piezoelectric film with a metal film according to claim 1, wherein the film substrate is uniaxially stretched.
6. The piezoelectric film with a metal film according to claim 1, wherein the film substrate contains an inorganic filler.
7. A device using a piezoelectric film with a metal film according to any one of claims 1 to 6.
8. A device obtained by photolithography of a piezoelectric film with a metal film according to any one of claims 1 to 6.
9. A mass detection device using the device described in claim 7 or claim 8.
Citation Information
Patent Citations
Macromolecular piezoelectric material and manufacturing method therefor
WO2012026494A1